Uji Daya Hidup Bakteri Asam Laktat Dari Usus Itik Pada Media Tumbuh Dengan Penambahan Variasi Konsentrasi Molasis - Sutrisna, Rudy; Ekowati, Christina Nugroho; Damayanti, Riska (Jurnal Penelitian Pertanian Terapan, 2016)
This study aims to determine differences in the viability of Lactic Acid Bacteria (LAB) isolates on MRS medium supplemented with various concentrations molasses. Concentration variation molasis used as controls were 0%, 1%, 2% and 3%. Variation of time incubation on each of the media that is 0 hours, 24 hours, 48 hours and 72 hours. The viability of each isolate was viewed with the population of Log (cells/ml) which grow on the medium and the number of generations and time of generations. The results showed that the concentration molasses added to MRS affect the viability of LAB. Concentration of 1% makes LAB better viability than controls. Total population continues to increase at the end of the incubation with a yield of 1.17 generations in time 20.46 hours/generation. In contrast to controls, reduced population size at the end of the incubation so as not to produce a generation. LAB viability in addition molasses 2% and 3% live on 48 hours of incubation. This is indicated by the number of population increased at 48 hours of incubation, and then decreased at the end of incubation. The addition of concentration variation in the types of bacteria showed different viability. At B1 adding molasses 2% and 3% live on 48 hours of incubation and control can only live on a 24 hours incubation, whereas the B3, the control can remain alive at 48 hours of incubation. In contrast to the controls on B4 can survive on 48 hours of incubation, whereas the addition of 3% molasses can only live on a 24 hours incubation. Key words : Lactic Acid Bacteria/LAB, Molasses,  Viability